Does Deltoid Ligament Repair Reduce Complications and Improve Functional Outcomes Measured by PROMIS Scores Following Ankle Fracture Surgery? - Steven M. Hadley BA; Rachel Bergman MD; John J. Peabody MD; Sarah J. Westvold MPH; Ryan Filler MD; Milap Patel DO; Anish R. Kadakia MD (Foot & Ankle Orthopaedics)
Background: Deltoid repair (DR) in ankle fracture surgery remains controversial. This study aims to determine whether DR reduces complications and improves outcomes measured by Patient Reported Outcomes Measurement Information System (PROMIS) computerized adaptive tests (CATs) of physical function (PF) and pain interference (PI). We hypothesized that DR would reduce complications and improve PROMIS scores. Methods: This was a retrospective study of 782 patients at a single institution who underwent ankle fracture surgery between January 2016 and December 2021. Two fellowship-trained foot and ankle orthopaedic surgeons independently reviewed all radiographs and assessed reduction quality and complications at final follow-up. Multiple extremity injuries, open fractures, and pilon variants were excluded. A total of 345 patients with deltoid ruptures were sent PROMIS CATs. Of those, 265 patients with minimum 1-year follow-up were analyzed for complications. Finally, 112 patients who completed CATs were analyzed for PROMIS. Wilcoxon rank-sum test compared PROMIS between groups. Linear regression modeled DR effect on PROMIS adjusted for relevant covariates and propensity scores. Results: Fifty of the 265 patients (18.9%) underwent DR. The incidence of radiographic evident complications among 215 patients (81.1%) without repair (NDR) was 14.42%: 7 (3.26%) degenerative joint disease, 3 (1.40%) ankle joint malreduction, 4 (1.86%) syndesmotic malreduction, and 8 (3.72%) malleolar malunion. The DR group had no radiographic complications. Among patients who completed CATs (n = 112), DR (n = 21) was not significantly different for mean PF (54.31±9.83 vs 52.79±10.42, P = .71) or mean PI (47.21±7.82 vs 48.53±8.37, P = .59) than NDR (n=91). Adjusted regression models estimated a 1.89-point increase in PF and a 1.67-point decrease in PI for DR vs NDR. When adjusted for propensity scores, DR had PF 2.17 higher and PI 1.73 lower compared to NDR. Neither of these reach minimal clinically important difference criteria. Conclusion: DR was associated with reduced radiographically evident complications following ankle fracture surgery. This study was underpowered to detect small effect sizes in PROMIS, and we remain uncertain if DR meaningfully improved patient-reported outcomes. Level of Evidence: Level IV, retrospective case series study.